Perjanjian Pinjam Nama sebagai Bentuk Kepemilikan Tanah oleh Warga Negara Asing di Bali - I Komang Gede Suwanjaya; I Nyoman Sumardika; Ni Made Puspasutari Ujianti (Jurnal Konstruksi Hukum, 2020)
A nominee agreement is an agreement that has not been specifically regulated in the Civil Code, but grows and develops in the community. The agreement is included in a special agreement or often called an innominate agreement. Based on this background, this research was conducted with the aim of describing the arrangement of nominee agreements as a form of land ownership by citizens in Bali and the responsibilities of notaries in drafting agreement deeds for land tenure by foreign nationals in Bali. The research method used was normative legal research. Based on the results, it was revealed that there was no specific regulation regarding the nominee agreement which was regulated in the Civil Code. As long as the parties are able to carry out the agreement properly in accordance with the provisions of the law regarding the validity of the agreement and regarding land ownership rights that have been regulated in the Civil Code and the Basic Agrarian Law, the agreement is valid before the law. Furthermore, the responsibilities and duties of a notary have been regulated in the Law on Notary Position. the ownership of land by a foreigner based on a nominee agreement is an act that is prohibited or against the law. The violation of the articles referred to in Article 84 of the Notary Position Law is a guarantee of the formal requirements for making an authentic deed. The government must supervise this anonymous agreement because this agreement is legal smuggling.